A distributed, predictive secondary control for voltage and frequency regulation, economic dispatch and imbalance sharing in isolated microgrids - Navas Fonseca, Alex Dario (2022)
Microgrids (MGs) are the cornerstone for a new model of electrical generation and distribution based on renewable resources. However, managing the operation of an MG is a challenging and complex task due to the characteristics of the various types of renewable sources and interactions between different types of generating equipment. In this context, some of the most pressing problems in MGs are associated with guaranteeing a cost-effective operation and the quality of the supply. Therefore, new and more reliable control strategies need to be developed for the management of microgrids. Distributed model predictive control (DMPC) is one of the best solutions for MGs as it can model complex systems and simultaneously address multiple objectives.